2018
DOI: 10.1016/j.mayocp.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Short Telomere Syndromes in Clinical Practice: Bridging Bench and Bedside

Abstract: Short telomere syndromes (STSs) are accelerated aging syndromes often caused by inheritable gene mutations resulting in decreased telomere lengths. Consequently, organ systems with increased cell turnover, such as the skin, bone marrow, lungs, and gastrointestinal tract, are commonly affected. Owing to diverse clinical presentations, STSs pose a diagnostic challenge, with bone marrow failure and idiopathic pulmonary fibrosis being frequent manifestations, occurring in association with gene mutations involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 74 publications
0
58
0
5
Order By: Relevance
“…Employing an inducible telomerase reverse transcriptase-estrogen receptor (TERT ER ) mouse model, it was demonstrated that persistent physiological DNA damage (from eroded telomeres) drives MDS in mice by inducing aberrant RNA splicing [110]. In human, short telomeres syndromes are also associated with accelerated aging syndromes characterized by diverse clinical manifestations and with bone marrow failure and idiopathic pulmonary fibrosis being frequent manifestations [111,112]. Similarly, skewing in X-chromosome inactivation has been more frequently detected in blood from elderly women [113] and deregulation of X-chromosome inactivation in the hematopoietic compartment is known to cause typical aging-like myelodysplastic syndromes (MDS) with 100% penetrance in mice [114].…”
Section: -20% 15%mentioning
confidence: 99%
“…Employing an inducible telomerase reverse transcriptase-estrogen receptor (TERT ER ) mouse model, it was demonstrated that persistent physiological DNA damage (from eroded telomeres) drives MDS in mice by inducing aberrant RNA splicing [110]. In human, short telomeres syndromes are also associated with accelerated aging syndromes characterized by diverse clinical manifestations and with bone marrow failure and idiopathic pulmonary fibrosis being frequent manifestations [111,112]. Similarly, skewing in X-chromosome inactivation has been more frequently detected in blood from elderly women [113] and deregulation of X-chromosome inactivation in the hematopoietic compartment is known to cause typical aging-like myelodysplastic syndromes (MDS) with 100% penetrance in mice [114].…”
Section: -20% 15%mentioning
confidence: 99%
“…In our experience, a pathogenic variant in the coding sequence of a telomere-associated gene can be identified in only 40% of STS cases using current sequencing approaches, with the remaining cases either having no identifiable variant or possessing a variant(s) of uncertain significance (VUS) 1,3 . In addition, in some of these cases, the TL values were not conclusively shortened (i.e., not < first percentile in lymphocytes and/or granulocytes documented by a CLIA-certified FlowFISH assay) complicating the diagnosis.…”
Section: Dear Editormentioning
confidence: 98%
“…Accelerated shortening of telomeres can induce premature cell senescence that can clinically manifest as bone marrow failure (BMF), idiopathic pulmonary fibrosis (IPF), cryptogenic cirrhosis, nodular regenerative hyperplasia, vascular malformations, immunodeficiency, and structural brain abnormalities, all of which are included under the umbrella term of short telomere syndromes (STSs) 1 . Two main criteria used to diagnose STS include the documentation of shortened telomere lengths (TLs) by a Clinical Laboratory Improvement Amendments (CLIA)-certified flowFISH (fluorescence in situ hybridization) assay 2 and the presence of pathogenic variants in genes related to telomere maintenance identified through next-generation sequencing (NGS).…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the production of reactive oxygen species associated with chronic inflammation, that can also be produced in response to chronic infection, several drugs and toxic products, or radiation exposure, also cause DNA damage and telomere loss [ 49 ]. Finally, inheritable gene mutations affecting the telomerase or the telomere protein complex, resulting in decreased telomere lengths (short telomere syndromes, STSs) [ 50 , 51 ]. These syndromes are characterized by severe alterations in hematopoiesis (bone marrow failure) and in organs with high cell turnover, such as skin (dyskeratosis), gastrointestinal tract (esophageal stenosis, enterocolitis, celiac-like enteropathy) and lungs (idiopathic pulmonary fibrosis) [ 50 , 51 ].…”
Section: Is a Major Driver Of Immunosenescencementioning
confidence: 99%